THE IMPLEMENTATION OF THE SYLLABUS WHICH CONTAINS LOCAL WISDOM AT X GRADE SMKN 1 PAYAKUMBUH - Normalasari; Veni Roza; Genta Sakti (ELLTER Journal, 2020)
Abstract: The research was due to the problem. The teacher had implemented the syllabus which contained local wisdom Minangkabau, but when the researcher saw the English textbook, the researcher found that there was no local wisdom included. This study used descriptive qualitative method as the paradigm in this research. The finding of this research reveals that the teacher included local wisdom in various ways. The first was when in a part of the introduction, the teacher included local wisdom through giving the motivation to the students, giving advice to students. The second was in a core activity the teacher included local wisdom through giving explanation before, through giving exercises. And the last in a part conclusion, the teacher included local wisdom through concluding the lesson and asking the students about the local wisdom related to a lesson. The result, the teacher implemented local wisdom values Minangkabau for increase character personality students.